Short pulse electron linac with full beam loading compensation - Mytrochenko, V.V.; Perezhogin, S.O.; Zhyglo, V.Ph.; Opanasenko, А.M. (Вопросы атомной науки и техники, 2020)
Acceleration of intense short-pulsed electron beams in transient mode with energy spread about a few tenths of a percent is the actual problem for RF linacs, in an instance, for an electron injector of a storage ring. In this work we study both analytically and numerically unsteady self-consistent beam dynamics in the one section RF linac fed from SLED. For compensation of the transient beam loading, resulting in beam energy spread, a method of a beam delay with respect to RF pulse is consider. In order to increase efficiency of this method we choose a homogenous dick-loaded waveguide with π/2 phase advance as an accelerating structure that characterized by the minimal frequency dispersion of group velocity. The preliminary results show that the full beam loading compensation is possible for the 1.2 A beam at its acceleration up to 60 MeV during 50 ns.